A Sociological Study of Literature on the Poetry Anthology 'Selama Laut Masih Bergerlombang' by Mariati Atkah: Coastal Life, Culture, and Life Transitions - Fitri Kamisah; Arini Putri Safira; Elsa Maharani; M. Fadillah Anugrah; Elmustian (Raja Zulkarnain Education Foundation, 2025)
This study aims to examine the representation of coastal community life in the poetry anthology